Highly Efficient Tandem Organic Solar Cell Enabled by Environmentally Friendly Solvent Processed Polymeric Interconnecting Layer. Issue 15 (12th February 2018) - Zhang, Kai; Fan, Baobing; Xia, Ruoxi; Liu, Xiang; Hu, Zhicheng; Gu, Honggang; Liu, Shiyuan; Yip, Hin‐Lap; Ying, Lei; Huang, Fei; Cao, Yong
Abstract: In the field of organic solar cells (OSCs), tandem structure devices exhibit very attractive advantages for improving power conversion efficiency (PCE). In addition to the well researched novel pair of active layers in different subcells, the construction of interconnecting layer (ICL) also plays a critical role in achieving high performance tandem devices. In this work, a new way of achieving environmentally friendly solvent processed polymeric ICL by adopting poly[(9, 9‐bis(3′‐( N, N ‐dimethylamino)propyl)‐2, 7‐fluorene)‐alt‐5, 5′‐bis(2, 2′‐thiophene)‐2, 6‐naphthalene‐1, 4, 5, 8‐tetracaboxylic‐ N, N ′‐di(2‐ethylhexyl)imide] (PNDIT‐F3N) blended with poly(ethyleneimine) (PEI) as the electron transport layer (ETL) and PEDOT:PSS as the hole transport layer is reported. It is found that the modification ability of PNDIT‐F3N on PEDOT can be linearly tuned by the incorporation of PEI, which offers the opportunity to study the charge recombination behavior in ICL. At last, tandem OSC with highest PCE of 12.6% is achieved, which is one of the best tandem OSCs reported till now. These results offer a new selection for constructing efficient ICL in high performance tandem OSCs and guide the way of design new ETL materials for ICL construction, and may even be integrated in future printed flexible large area module device fabrication with the advantages of environmentally friendly solvent processing and thickness insensitivity. Abstract : A new polymeric interconnecting layer (ICL) based on poly[(9, 9‐bis(3′‐( N, N ‐dimethylamino)propyl)‐2, 7‐fluorene)‐alt‐5, 5′‐bis(2, 2′‐thiophene)‐2, 6‐naphthalene‐1, 4, 5, 8‐tetracaboxylic‐ N, N ′‐di(2‐ethylhexyl)imide]: poly(ethyleneimine)/PEDOT:PSS is developed and applied for the fabrication of high performance tandem organic solar cells (OSCs). Tandem OSCs employing this ICL achieve a high power conversion efficiency of 12.6% with ICL thickness of 60 nm and even reach to 11.3% with ICL thickness of 140 nm.